EVALUATION OF GROUNDWATER QUALITY IN COASTAL AREAS: IMPLICATIONS FOR SUSTAINABLE AGRICULTURE - Lee J.; Song S. (My University, 2007)
Seawater intrusion is a problem in the coastal areas of Korea. Most productive agricultural fields are in the western and southern coastal areas of the country where irrigation predominantly relies on groundwater. Seawater intrusion has affected agricultural productivity. To evaluate progressive encroachment of saline water, the Korean government established a seawater intrusion monitoring well network, especially in the western and southern part of the peninsula. Automatic water levels and EC monitoring and periodic chemical analysis of groundwater help track salinization. Salinization of fresh groundwater is highly associated with groundwater withdrawal. A large proportion of the groundwaters are classified as Na–Cl and Ca–Cl types. The Na–Cl types represent effects of seawater intrusion. The highest EC level was over 1.6 km inland and high Cl values were observed up to 1.2 km inland. Lower ratios of Na/Cl and SO4/Cl than seawater values indicate the seawater encroachment. A linear relation between Na and Cl represents simple mixing of the fresh groundwater with the seawater. The saline Na–Cl typed groundwaters showed Br/Cl ratios similar to or less than seawater values. The Ca–HCO3 type groundwaters had the highest Br/Cl ratios. Substantial proportions of the groundwaters showed potential for salinity and should be better managed for sustainable agriculture.
Keywords: SEAWATER INTRUSION; GROUNDWATER MONITORING NETWORK; COASTAL AQUIFERS; AGRICULTURE; ELECTRICAL CONDUCTIVITY; CHLORIDE; KOREA